(3efGbH GdYTQIs - (3GdReNTQis; (3MGRe GdbQWGLfj , MGRe Hf eMeO Hf MSf Hf MGRe, CHh GdMSf,J (B684 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI Ydi QShd Gddg hHYO aEfg hQO ai UMjM GdCKGQ GdeSfOI Yf GdYdeGA GdcHGQ Cf QShd Gddg Udi Gddg Ydjg hSde bGd YfO PcQ GdUGdMjf JfRd GdQMeI GdMOjK s
(3BNQgG (B:s
(3GdChGFd hGdChGNQ jG SjOi jG QShd Gddg Gddge TaYg ajfG GfJgi s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B159s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs